Comparison of Mw3.30 and Mw++, a Windows version of pharmacokinetic software for PK/PD monitoring of vancomycin. Part 1: A-posteriori modelling. (February 2022) - Schön, Kristyna; Koristkova, Blanka; Kacirova, Ivana; Brozmanova, Hana; Grundmann, Milan
Highlights: The Windows version of the MWsoftware (MEDI, Prague, Czechia/ Groningen, Netherlands) offers three 2-compartment models for TDM of vancomycin for adult patients: " vancomycin_adult_k_C2", "#vancomycin_adult_C2" and "vancomycin_adult_C2" . Both DOS and Windows software versions can be used for therapeutic data monitoring (TDM) of vancomycin interchangeably. The best outcomes were reached with the "vancomycin_adult_C2" model. The addition of the DOS vancomycin model into the Windows software version is recommended. Abstract: Background and Objectives: For a long time, the Mwsoftware suite (MEDI, Prague, Czech Republic/ Groningen, Netherlands) has been used for PK/PD modelling in therapeutic drug monitoring (TDM). The aim of this study was to find the best model in the newer Windows Mw++ 1.3.5.558 version (WIN). Methods: 25 patients were repeatedly examined for vancomycin (mean age 63±14 years, body weight 88±21 kg, median dose 1 g/12 h). Trough concentrations predicted a-posteriori by WIN models " vancomycin_adult_k_C2", "#vancomycin_adult_C2", "vancomycin_adult_C2" were compared with the measured value and "vancomycin adult" DOS 3.30 model (DOS). Statistics: Percentage prediction error (%PE) calculated as (predicted–measured)/measured values, or WIN-DOS/DOS - data presented as mean±SD, RMSE, Blandt-Altman plot - data presented as bias±SD (95% limits of agreement), Pearson's coefficient of rank correlation (R), Student's t -test. Statistical analysis was performed using GraphPad Prism version 5.00 for Windows. Results: The mean%PE in vancomycin predicted values varied from -4.5% ± 33.6 to -8.2% ± 39.3. The%PE between WIN and DOS models varied from -0.2% ± 24.5% to 4.4 ± 21.4%. Model "vancomycin_adult_C2" was closest both to measured vancomycin trough concentration and DOS model:%PE -4.5 ± 33.6% vs +4.2 ± 20.3%, RMSE 33.7 vs 20.6, Blandt-Altman bias +2.19 ± 6.17 (-9.9 – 14.3) vs -0.29 ± 3.25 (-6.7 – 6.1), resp. "#vancomycin_adult_C2" model produced largest%PE (-8.2%), RMSE (40.0) as well as Blandt-Altman bias +2.82 ± 6.76 (-10.4 – 16.1). The Pearson's R of predicted and measured vancomycin concentration, and of values predicted by WIN and DOS models, varied from 0.5135 to 0.5854, P <0.0001 and from 0.7869 to 0.8462, P <0.0001, resp. Conclusions: Three Windows vancomycin models and one DOS model in the Mwsoftware were compared. The best outcomes, i.e. lowest%PE, RMSE and highest Pearson's R, were reached with "vancomycin_adult_C2" model.